Antibiotic-Resistant Escherichia coli in Women with Acute Cystitis in Canada. Issue 3 (2013) - McIsaac, Warren J; Moineddin, Rahim; Meaney, Christopher; Mazzulli, Tony
Abstract : BACKGROUND: Trimethoprim-sulfamethoxazole (TMP-SMX) has been a traditional first-line antibiotic treatment for acute cystitis; however, guidelines do not recommend TMP-SMX in regions where Escherichia coli resistance exceeds 20%. While resistance is increasing, there are no recent Canadian estimates from a primary care setting to guide prescribing decisions. METHODS: A total of 330 family physicians assessed 752 women with suspected acute cystitis between 2009 and 2011. Physicians documented clinical features and collected urine for cultures for 430 (57.2%) women. The proportion of resistant isolates of E coli and exact binomial 95% CIs were estimated nationally, and compared regionally and demographically. These estimates were compared with those from a 2002 national study. RESULTS: The proportion of TMP-SMX-resistant E coli was 16.0% nationally (95% CI 11.3% to 21.8%). This was not statistically higher than 2002 (10.9% [P=0.14]). TMP-SMX resistance was increased in women ≤50 years of age (21.4%) compared with older women (10.7% [P=0.037]). In women with no antibiotic exposure in the previous three months, TMP-SMX-resistant E coli remained more prevalent in younger women (21.8%) compared with older women (4.4% [P=0.003]). The proportion of ciprofloxacin-resistant E coli was 5.5% nationally (95% CI 2.7% to 9.9%), and was increased compared with 2002 (1.1% [P=0.036]). Ciprofloxacin resistance was highest in British Columbia (17.7%) compared with other regions (2.7% [P=0.003]), and was increased compared with 2002 levels in this province (0.0% [P=0.025]). Nitrofurantoin-resistant E coli levels were low (0.5% [95% CI 0.01% to 2.7%). DISCUSSION: The proportion of TMP-SMX-resistant E coli causing acute cystitis in women in Canada remains below 20% nationally, but may exceed this level in premenopausal women. Ciprofloxacin resistance has increased, notably in British Columbia. Nitrofurantoin resistance levels are low across the country. These observations indicate that TMP-SMX and nitrofurantoin remain appropriate empirical antibiotic agents for treating cystitis in primary care settings in Canada.